Steel sheet and method for producing the same

By controlling the microstructure and composition of the steel sheet, including specific fractions of ferrite and island-like martensite, the steel sheet achieves high tensile strength, excellent toughness, and a low yield ratio, addressing the limitations of existing steel sheets and reducing material costs.

JP2025048749AActive Publication Date: 2025-04-03JFE STEEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024134878
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-08-13
Publication Date
2025-04-03
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

Existing steel sheets with low yield ratios and excellent toughness at low temperatures cannot achieve high tensile strengths of 690 MPa or higher, leading to the necessity of using expensive nickel steel for applications like large liquefied gas storage tanks.

Method used

A steel sheet composition with specific microstructural control, including a ferrite fraction of 5-95%, an island-like martensite fraction of 1-30%, and tempered martensite and/or bainite, along with a solid solution C content in island-like martensite less than 0.4% and an island-like martensite decomposition rate of less than 50%, is developed to achieve the desired properties.

Benefits of technology

The steel sheet achieves excellent toughness and a low yield ratio in high-strength steels with a tensile strength of 690 MPa or higher, reducing material costs compared to nickel steel and enabling its use in large low-temperature storage tanks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048749000001
    Figure 2025048749000001
  • Figure 2025048749000002
    Figure 2025048749000002
  • Figure 2025048749000003
    Figure 2025048749000003
Patent Text Reader

Abstract

To provide a steel sheet and a method for producing the same.SOLUTION: A steel sheet according to the present invention comprises, in mass%, 0.02% to 0.15% of C, 0.01% to 0.50% of Si, 0.05% to 2.50% of Mn, 0.50% to less than 5.00% of Ni, 0.03% or less of P, 0.005% or less of S, and 0.0080% or less of N, with the remainder being Fe and unavoidable impurities. The microstructure at a depth position corresponding to 1 / 4 of the sheet thickness has, in terms of area fraction, a ferrite fraction of 5-95% and an island-like martensite fraction of 1-30%, with the remainder being tempered martensite and / or bainite, wherein the amount of solid-solution C in the island martensite is less than 0.4%, and the decomposition ratio of the island martensite is less than 50%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel plate capable of stably ensuring excellent strength, toughness and a low yield ratio and suitable for use at low temperatures, and a method for producing the same. [Background technology]

[0002] In the case of a ship liquefied gas storage tank that is an independent Type-C tank and has a design temperature lower than -10°C, when carbon steel or carbon manganese steel is used as the steel, stress relief is required after welding the steel. This stress relief is usually performed by PWHT (Post Weld Heat Treatment), but if the yield ratio of the steel is 0.8 or less, it is also possible to mechanically relieve the stress. Therefore, since it becomes difficult to perform PWHT when the tank is large, it is desirable to use a material with a low yield ratio that allows mechanical stress relief as the steel of the tank. For example, when carbon steel is used for a large storage tank for liquefied CO2, a high-strength steel with a tensile strength (hereinafter also referred to as "TS") of 690 MPa or more is required while maintaining excellent toughness at low temperatures of -50 to -70°C. Therefore, there is a demand to provide a steel material that has a low yield ratio, i.e., excellent ductility, high strength, and excellent toughness at low temperatures.

[0003] As an example of a steel plate having a low yield ratio and excellent toughness at low temperatures, Patent Document 1 discloses a steel plate having an impact toughness of 150 J at -75°C, a yield ratio of 0.8 or less, and a tensile strength of 530 MPa or more. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2016-507649 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the steel plate described in Patent Document 1 has a TS of 620 MPa at most, and no steel plate with a TS of 690 MPa or more has been provided. As described above, in the past, no carbon steel was provided that has a low yield ratio, excellent toughness at low temperatures, and high strength with a TS of 690 MPa or more. This has forced the use of expensive nickel steel, such as 9% Ni steel, resulting in a problem of high material costs.

[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a steel plate that is a high-strength steel with a TS of 690 MPa or more and that achieves excellent toughness and a low yield ratio at low temperatures, and a method for manufacturing the same. [Means for solving the problem]

[0007] In order to achieve the above object, the present inventors have conducted extensive research into component compositions and microstructures that achieve toughness (hereinafter also simply referred to as "toughness") and a low yield ratio at low temperatures on the premise of high-strength steel, and have made the following findings, particularly regarding the microstructure.

[0008] Specifically, it has been newly discovered that the microstructure at a depth of 1 / 4 of the plate thickness from the surface of the steel plate in the plate thickness direction has an area fraction of 5 to 95% ferrite, 1 to 30% island martensite, and the remainder tempered martensite and / or bainite, and that appropriately controls the amount of solute C in the island martensite and the decomposition rate of the island martensite to cementite (i.e., the "island martensite decomposition rate" described below), is effective in improving the desired properties.

[0009] Here, the above-mentioned ferrite refers to the BCC phase that does not reverse transform even when martensite or bainite is heat-treated at a temperature of the Ac1 point or higher and remains, inheriting the original lath-shaped structure. The present inventors have found that by performing heating and accelerated cooling in the two-phase region, this relatively soft ferrite can be made to account for 5 to 95% in area ratio, and island martensite can be finely dispersed within the above numerical range, thereby achieving a low yield ratio.

[0010] They also discovered that tempering at a tempering temperature of 100°C or higher but lower than 300°C reduces the amount of excessive dissolved C in island martensite while suppressing the decomposition of island martensite into cementite, thereby making it possible to ensure toughness while maintaining a low yield ratio.

[0011] The present invention has been completed based on the above findings, and the gist of the present invention is as follows. [1] In weight percent: C: 0.02% or more and 0.15% or less, Si: 0.01% or more and 0.50% or less, Mn: 0.05% or more and 2.50% or less, Ni: 0.50% or more and less than 5.00% P: 0.03% or less, S: 0.005% or less, and N: 0.0080% or less The remainder of the composition is Fe and unavoidable impurities. The microstructure at a depth of 1 / 4 of the plate thickness from the surface of the steel plate in the plate thickness direction is as follows: In terms of area fraction, the ferrite fraction is 5 to 95%, the island martensite fraction is 1 to 30%, and the remainder is tempered martensite and / or bainite; The steel plate has a solute C content in the island martensite of less than 0.4% and a decomposition rate of the island martensite of less than 50%. [2] The composition further comprises, in mass%, Al: 0.100% or less, Nb: 0.1% or less, Cr: 2.00% or less, Mo: 1.0% or less Cu: 2.00% or less, V: 0.10% or less, Ti: 0.03% or less, B: 0.0050% or less, Ca: 0.0070% or less, REM: 0.010% or less, Mg: 0.0070% or less, and Zr: 0.0050% or less The steel sheet according to [1], containing one or more selected from the following: [3] The steel sheet according to [1] or [2], wherein the microstructure has an average crystal grain thickness of 30 μm or less. [4] A method for producing a steel sheet according to any one of [1] to [3], A steel material having the above-mentioned composition is heated and hot-rolled to obtain a hot-rolled steel sheet; Next, the hot-rolled steel sheet is subjected to a two-phase region quenching process in which the heating time from Ac1 point to (Ac1 point + 50°C) at the center of the sheet thickness is 2000 seconds or less, and the heating temperature is a two-phase region temperature range of (Ac1 point + 50°C) or more and less than Ac3 point at the center of the sheet thickness, and then accelerated cooling is performed under conditions in which the average cooling rate in the temperature range of 700°C or less and 500°C or more at a temperature at a depth position of 1 / 4 of the sheet thickness is 3°C / second or more, and the cooling end temperature is less than 500°C at a temperature at a depth position of 1 / 4 of the sheet thickness, Next, a tempering step is performed in which the steel plate is tempered at a tempering temperature of 100°C or higher and lower than 300°C at the center of the plate thickness. [5] Prior to the two-phase intercritical quenching step, The method for producing a steel plate according to [4], further comprising the steps of: heating and holding the hot-rolled steel plate at a heating temperature of not less than Ac3 and not more than 1000°C at the center of the plate thickness; and then performing an accelerated cooling process under conditions in which the average cooling rate in the temperature range of not more than 700°C and not less than 500°C at a temperature at a depth position of 1 / 4 of the plate thickness is 3°C / sec or more; and the cooling end temperature is less than 300°C at a temperature at a depth position of 1 / 4 of the plate thickness. Effect of the Invention

[0012] According to the present invention, it is possible to realize excellent toughness and a low yield ratio at low temperatures in a high-strength steel having a TS of 690 MPa or more. Therefore, the steel plate of the present invention, although being a carbon steel or a carbon-manganese steel, can be used as a steel material for steel structures used in low-temperature environments, such as large cryogenic storage tanks for ships, for example, liquefied CO2 tanks and LPG tanks. Furthermore, the steel plate of the present invention can reduce the construction cost compared to nickel steel. Therefore, the present invention brings about a significant effect in the industry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the embodiments of the present invention will be described in detail. Note that the following description shows a preferred embodiment of the present invention, and the present invention is not limited thereto.

[0014] <Steel plate> First, the steel sheet of the present invention will be described.

[0015] [Component composition] The steel plate of the present invention has the following specified composition. The steel material used to manufacture the steel plate of the present invention, which will be described later, also has the specified composition. Each element contained in this composition will be explained below. In this specification, "%" used as a unit of the content of each element means "% by mass" unless otherwise specified.

[0016] C: 0.02% or more and 0.15% or less C is an element that has the effect of improving the strength of a steel plate. To obtain this effect, the C content is set to 0.02% or more. The C content is preferably 0.03% or more, and more preferably 0.04% or more. On the other hand, if the C content exceeds 0.15%, the amount of island martensite in the steel plate increases and the toughness decreases. Therefore, the C content is set to 0.15% or less. The C content is preferably 0.12% or less, and more preferably 0.10% or less.

[0017] Si: 0.01% or more and 0.50% or less Si is an element that acts as a deoxidizer. In order to exert this effect, the Si content is set to 0.01% or more. The Si content is preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, if the Si content is excessively high, the toughness decreases. Therefore, the Si content is set to 0.50% or less. The Si content is preferably 0.40% or less, and more preferably 0.30% or less.

[0018] Mn: 0.05% or more and 2.50% or less Mn is an element that improves the hardenability of steel and is effective in increasing the strength of steel plate. To obtain this effect, the Mn content is set to 0.05% or more. The Mn content is preferably 0.10% or more, and more preferably 0.20% or more. On the other hand, if the Mn content exceeds 2.50%, the toughness is deteriorated, so the Mn content is set to 2.50% or less. The Mn content is preferably 2.00% or less, and more preferably 1.80% or less.

[0019] Ni: 0.50% or more and less than 5.00% Ni is an element effective in improving the toughness of steel plate. To obtain this effect, the Ni content is set to 0.50% or more. On the other hand, since Ni is an expensive element, the steel plate cost increases as the Ni content increases. Therefore, in the present invention, the Ni content is set to less than 5.00%. The Ni content is preferably 0.80% or more and preferably 3.50% or less. The Ni content is more preferably 1.50% or more and more preferably 3.00% or less.

[0020] P:0.03% or less P is an inevitable impurity and a harmful element that adversely affects the toughness of steel plates. For example, in order to obtain a sound base material and welded joint when steel plates are welded to form a welded structure, it is desirable to reduce the P content as much as possible. Therefore, in the present invention, the P content is suppressed to 0.03% or less. From the viewpoint of toughness, the lower the P content, the better, so the lower limit of the P content is not particularly limited and may be 0%, but even in that case, it is permitted to contain P as an inevitable impurity. On the other hand, excessive reduction of P causes an increase in cost, so from the viewpoint of cost, it is preferable to set the lower limit of the P content to 0.001% or more.

[0021] S: 0.005% or less Since S forms MnS in steel and significantly deteriorates toughness, it is desirable to reduce the S content as much as possible, with an upper limit of 0.005%. Therefore, the S content is set to 0.005% or less. The S content is preferably set to 0.002% or less. On the other hand, since the lower the S content, the better, the lower limit of the S content is not particularly limited and may be 0%, but even in that case, it is acceptable to include S as an unavoidable impurity. From the viewpoint of cost, the S content is preferably set to 0.0002% or more.

[0022] N: 0.0080% or less N forms precipitates in steel, and if the N content exceeds 0.0080%, it causes a decrease in toughness. Therefore, the N content is set to 0.0080% or less. The N content is preferably set to 0.0060% or less, and more preferably set to 0.0050% or less. The N content is preferably set to 0.0010% or more.

[0023] The basic composition of the steel sheet of the present invention is made up of the above-mentioned elements in the prescribed amounts, with the balance being Fe and unavoidable impurities.

[0024] With this basic composition, the steel sheet of the present invention can obtain the desired properties. In addition to this basic composition, the present invention may optionally contain one or more elements selected from Al, Nb, Cr, Mo, Cu, V, Ti, B, Ca, REM, Mg, and Zr in order to further improve the properties. Note that each of Al, Nb, Cr, Mo, Cu, V, Ti, B, Ca, REM, Mg, and Zr may be contained as necessary, and therefore these elements may be 0%.

[0025] One or more selected from Al: 0.100% or less, Nb: 0.1% or less, Cr: 2.00% or less, Mo: 1.0% or less, Cu: 2.00% or less, V: 0.10% or less, Ti: 0.03% or less, B: 0.0050% or less, Ca: 0.0070% or less, REM: 0.010% or less, Mg: 0.0070% or less, and Zr: 0.0050% or less

[0026] Al: 0.100% or less Al is an element that acts as a deoxidizer, and is most commonly used in the molten steel deoxidation process for high tensile steel. In order to obtain this effect, when Al is contained, the Al content is preferably 0.001% or more. The Al content is more preferably 0.010% or more. On the other hand, when the Al content exceeds 0.100%, there is a risk of a decrease in toughness. Therefore, when Al is contained, the Al content is preferably 0.100% or less. The Al content is more preferably 0.07% or less.

[0027] Nb: 0.1% or less Nb is an element that contributes to improving the strength of steel, and can be included at any amount depending on the desired strength. However, if the Nb content exceeds 0.1%, there is a risk of the toughness deteriorating. Therefore, when Nb is included, the Nb content is preferably 0.1% or less. From the viewpoint of obtaining the strength improving effect of Nb, the Nb content is preferably 0.005% or more. The Nb content is more preferably 0.010% or more.

[0028] Cr:2.00% or less Cr is an element that can improve the strength of a steel plate without significantly impairing toughness. In order to obtain the above effect, when Cr is contained, the Cr content is preferably 0.01% or more. The Cr content is more preferably 0.30% or more. However, if the Cr content exceeds 2.00%, the toughness of the steel plate may decrease. Therefore, when Cr is contained, the Cr content is preferably 2.00% or less. The Cr content is more preferably 0.80% or less.

[0029] Mo: 1.0% or less Mo is an element that contributes to improving the strength of steel, and can be included at any amount depending on the desired strength. However, if the Mo content exceeds 1.0%, there is a risk of the toughness deteriorating, so if Mo is included, the Mo content is preferably 1.0% or less. The Mo content is more preferably 0.80% or less. From the viewpoint of obtaining the strength improving effect of Mo, the Mo content is preferably 0.01% or more. The Mo content is more preferably 0.05% or more.

[0030] Cu:2.00% or less Cu is an element capable of increasing strength while maintaining high toughness, and can be optionally contained according to the desired strength. However, if the Cu content exceeds 2.00%, hot brittleness may occur, and the surface properties of the steel sheet may deteriorate. Therefore, when Cu is contained, the Cu content is preferably 2.00% or less. The Cu content is more preferably 1.00% or less. In order to obtain the above effects, when Cu is contained, the Cu content is preferably 0.01% or more. The Cu content is more preferably 0.10% or more, and even more preferably 0.20% or more.

[0031] V: 0.10% or less V is an effective element that can increase the strength of a steel sheet by precipitation strengthening. However, if the V content is excessively high, the toughness of the steel sheet may decrease. Therefore, when V is contained, the V content is preferably 0.10% or less. The V content is more preferably 0.05% or less, and further preferably 0.04% or less. When V is contained to obtain the above effect, the V content is preferably 0.010% or more.

[0032] Ti: 0.03% or less Ti is an element that has the effect of increasing the toughness of the weld without degrading the mechanical properties of the base material when steel plates are welded to form a welded structure. When Ti is contained to obtain the above effect, it is preferable that Ti is contained in an amount of 0.003% or more. On the other hand, if the Ti content exceeds 0.03%, there is a risk that the toughness may be decreased. Therefore, when Ti is contained, it is preferable that Ti is contained in a range of 0.03% or less. It is more preferable that the Ti content is 0.01% or more.

[0033] B: 0.0050% or less B is an element that improves hardenability when added in small amounts. When B is contained to effectively exert this effect, it is preferable that B is contained in an amount of 0.0003% or more. On the other hand, if the B content exceeds 0.0050%, toughness may deteriorate. Therefore, when B is contained, it is preferable that the B content is 0.0050% or less. It is more preferable that the B content is 0.0030% or less.

[0034] Ca:0.0070% or less Ca is an element that has the effect of improving the toughness of a steel plate by controlling the morphology of inclusions in the steel. However, if the Ca content is excessively high, the cleanliness of the steel may be impaired, and the Charpy absorbed energy (hereinafter also referred to as "Charpy toughness") at low temperatures may be reduced. Therefore, when Ca is contained, the Ca content is preferably 0.0070% or less. The Ca content is more preferably 0.0040% or less. Note that, when Ca is contained in order to obtain the above effect, the Ca content is preferably 0.0010% or more.

[0035] REM: 0.010% or less Like Ca, REM (rare earth metal) is an element that has the effect of improving the toughness of steel plate by controlling the morphology of inclusions in steel. However, if the REM content is excessively high, the cleanliness of the steel may be impaired and the Charpy toughness may decrease. Therefore, when REM is contained, the REM content is preferably 0.010% or less. The REM content is more preferably 0.008% or less. Note that, when REM is contained in order to obtain the above effect, the REM content is preferably 0.001% or more.

[0036] Here, REM is a collective term for 17 elements, including 15 lanthanoid elements, Y, and Sc, and these elements can be contained alone or in combination. Therefore, the content of REM means the total content of these elements.

[0037] Mg: 0.0070% or less Like Ca and REM, Mg is an element that has the effect of improving the toughness of a steel plate by controlling the form of inclusions in the steel. However, if the Mg content is excessively high, the cleanliness of the steel may be impaired and the Charpy toughness may decrease. Therefore, when Mg is contained, the Mg content is preferably 0.0070% or less. The Mg content is more preferably 0.0040% or less. In addition, when Mg is contained in order to obtain the above effect, the Mg content is preferably 0.0010% or more.

[0038] Zr: 0.0050% or less Zr, like Ca and Mg, is an element effective in controlling the shape of inclusions such as MnS, and can be contained as necessary. Through controlling the shape of these inclusions, toughness and resistance to sulfide stress corrosion cracking can be improved. When Zr is contained in order to obtain such effects, the Zr content is preferably 0.0005% or more. The Zr content is more preferably 0.0010% or more. On the other hand, if a large amount of Zr is contained, the amount of nonmetallic inclusions increases, which may impair the cleanliness of the steel and reduce the Charpy toughness. Therefore, when Zr is contained, the Zr content is 0.0050% or less. The Zr content is more preferably 0.0040% or less.

[0039] [Microstructure] In the steel plate of the present invention, the microstructure at a depth of 1 / 4 of the plate thickness from the surface of the steel plate in the plate thickness direction has, in terms of area fraction, a ferrite fraction of 5 to 95%, an island martensite fraction of 1 to 30%, and the remaining structure being tempered martensite and / or bainite, and further, the amount of solute C in the island martensite is less than 0.4%, and the island martensite decomposition rate is less than 50%.

[0040] Here, each structure in the present invention will be described. The above-mentioned ferrite refers to the BCC phase that remains without reverse transformation even when the martensite or bainite formed during hot rolling or γ-region quenching process is heat-treated at a temperature above the Ac1 point, and that inherits the original lath-shaped structure. The above martensite refers to martensite formed during the two-phase region quenching process, in which there is no island martensite between the laths and in which carbide precipitation cannot be confirmed by structural observation. The above-mentioned island martensite refers to martensite that is generated between laths of bainite during the two-phase region quenching process and has a high carbon concentration. The above-mentioned tempered martensite refers to martensite that has been produced in the two-phase region quenching process and has been tempered, and in which carbide precipitation can be confirmed by structural observation. The above-mentioned bainite refers to bainite that is formed during the two-phase region quenching process, in which island martensite is confirmed between the laths and carbides are confirmed in the structure. In the present invention, the "hard phase" refers to island martensite, tempered martensite, and bainite.

[0041] Ferrite fraction: 5 to 95% by area When the ferrite fraction in the microstructure is less than 5%, the yield ratio does not satisfy the requirement of 0.80 or less. This is for the following reason. When the ferrite fraction is less than 5%, the amount of the softest ferrite phase becomes insufficient, and the YS cannot be sufficiently lowered, resulting in a yield ratio exceeding 0.8. Therefore, the ferrite fraction is set to 5% or more. The ferrite fraction is preferably 10% or more, and more preferably 15% or more.

[0042] On the other hand, if the ferrite fraction exceeds 95%, the fraction of island martensite is low, and the yield ratio does not satisfy the requirement of 0.80 or less. Therefore, the ferrite fraction is set to 95% or less. The ferrite fraction is preferably 90% or less, and more preferably 85% or less.

[0043] Island martensite fraction: 1 to 30% by area If the island martensite fraction is less than 1%, the yield ratio does not satisfy 0.80 or less. This is for the following reason. If the island martensite fraction is less than 1%, the hard phase becomes insufficient and the yield ratio of 0.80 or less cannot be stably achieved. Therefore, the island martensite fraction is set to 1% or more. The island martensite fraction is preferably 3% or more, and more preferably 5% or more.

[0044] On the other hand, if the island martensite fraction exceeds 30%, the hard phase that may cause brittle fracture becomes excessive, and brittle fracture may occur. As a result, toughness deteriorates. Therefore, the island martensite fraction is set to 30% or less. The island martensite fraction is preferably 25% or less, and more preferably 22% or less.

[0045] Remaining structure: tempered martensite and / or bainite The balance other than ferrite and island martensite is tempered martensite and / or bainite, that is, the balance is one or two selected from tempered martensite and bainite.

[0046] If the remaining structure is not tempered martensite and / or bainite, for example as-quenched martensite, the toughness desired in the present invention is not satisfied for the following reason: if the remaining structure contains as-quenched martensite, the hardness will be excessive, but since as-quenched martensite is a brittle structure, brittle fracture will occur, and as a result, the toughness value targeted in the present invention will not be satisfied.

[0047] The fraction of the remaining structure, as the total area ratio of each structure, is preferably 4 to 94%, more preferably 20% or more and more preferably 80% or less.

[0048] The fractions of the above-mentioned structures of ferrite, island martensite, tempered martensite, bainite, and martensite can be measured by the method described in the examples below.

[0049] Amount of solute C in island martensite: less than 0.4% When the amount of solute C in the island martensite is 0.4% or more, the toughness decreases, i.e., a brittle fracture occurs. In the present invention, the "amount of solute C in the island martensite" refers to the average C concentration in the island martensite region measured by FE-EPMA. This is for the following reason. If the amount of solute C in the island martensite is 0.4% or more, the hardness becomes excessive. This makes brittle fracture more likely to occur, and reduces the Charpy absorbed energy. Therefore, the amount of solute C in the island martensite is set to less than 0.4%. The amount of solute C is preferably 0.3% or less.

[0050] In the present invention, there is no particular lower limit for the amount of solute C in the island martensite. From the viewpoint of lowering the yield ratio, the amount of solute C is preferably 0.2% or more.

[0051] The amount of solute C in the island martensite can be measured by the method described in the examples below.

[0052] Island martensite decomposition rate: less than 50% If the island martensite decomposition rate is 50% or more, it becomes difficult to satisfy the low yield ratio. Here, the above-mentioned "low yield ratio" refers to a yield ratio of 0.8 or less. The above-mentioned "island martensite decomposition rate" refers to the proportion (area proportion) of island martensite in which carbides have been precipitated by tempering, among all island martensite. In the present invention, an island martensite region in which carbide precipitation due to tempering has been confirmed is judged to be "decomposed island martensite".

[0053] The reason for specifying the island martensite decomposition rate in the present invention is as follows. When the island martensite decomposition rate is 50% or more, even if the amount of island martensite that remains undecomposed is sufficient, the hardness difference between the undecomposed island martensite and the surrounding structure is reduced, and as a result, the low yield ratio is not satisfied. Therefore, the island martensite decomposition rate is set to less than 50%. The island martensite decomposition rate is preferably 47% or less, more preferably 40% or less, and even more preferably 30% or less.

[0054] In the present invention, the lower limit of the island martensite decomposition rate is not particularly specified. That is, the island martensite decomposition rate may be 0%. The island martensite decomposition rate of 0% is a state in which the island martensite has a sufficient hardness difference with the surrounding structure, and is a state in which the lowest yield ratio can be obtained.

[0055] The island martensite decomposition rate can be measured by the method described in the examples below.

[0056] The steel sheet of the present invention has a microstructure having the above-mentioned configuration, thereby obtaining the mechanical properties described below. In the present invention, in order to further improve the mechanical properties, the microstructure at a depth position of ¼ of the sheet thickness may have the following configuration in addition to the above-mentioned configuration.

[0057] Average grain thickness: 30μm or less (optional condition) In the microstructure at a depth position of 1 / 4 of the plate thickness from the surface of the steel plate in the plate thickness direction, the average crystal grain thickness (i.e., the average crystal grain thickness) is desirably 30 μm. This is because by controlling this average crystal grain thickness, a fine grain structure can be achieved and the desired toughness can be ensured. Here, the above-mentioned "crystal grain" refers to the region surrounded by grain boundaries with a grain boundary orientation difference of 15 degrees or more, and the above-mentioned "average crystal grain thickness" refers to the average length of the crystal grains in the plate thickness direction. The above-mentioned average crystal grain thickness can be measured by the method described in the examples below.

[0058] The average thickness of the crystal grains can be controlled to fall within the above numerical range by controlling the cooling rate in the quenching step to 3° C. / sec or more.

[0059] Plate Thickness The thickness of the steel plate of the present invention is not particularly limited. As described above, from the viewpoint of applying the steel plate of the present invention to the steel material of steel structures used in low-temperature environments such as large-scale low-temperature storage tanks for ships, for example, liquefied CO2 tanks and LPG tanks, that is, from the viewpoint of using the steel plate of the present invention as a steel plate for tanks, the plate thickness is preferably 6 mm or more and 50 mm or less. The plate thickness is more preferably 20 mm or more, even more preferably 25 mm or more, and even more preferably 30 mm or more.

[0060] [Mechanical properties] The steel sheet of the present invention having the above-described component composition and microstructure has the following mechanical properties.

[0061] (Tensile strength) The lower limit of the tensile strength (TS) of the steel plate is preferably 690 MPa or more. This is because the plate thickness can be reduced when the steel plate is applied to a tank. The tensile strength is more preferably 720 MPa or more. On the other hand, there is no particular upper limit to the tensile strength. The upper limit of the tensile strength is preferably 1000 MPa or less. Here, "high strength" in the present invention refers to a TS of the steel plate of 690 MPa or more.

[0062] The tensile strength can be measured by the method described in the Examples section below.

[0063] (yield ratio) The upper limit of the yield ratio (YR) of the steel plate is preferably 0.80 or less. This is because mechanical stress relief can be applied instead of PWHT (post-weld heat treatment) as a method for stress relief after welding of the steel plate. The yield ratio is more preferably less than 0.80. On the other hand, the lower limit of the yield ratio of the steel plate is not particularly limited. The yield ratio is preferably 0.60 or more.

[0064] The yield ratio can be determined by the method described in the examples below.

[0065] (Toughness) The toughness value of the steel plate is the Charpy absorbed energy (vE -50℃ ) is preferably 100J or more in a full-size Charpy impact test and 50J or more in a half-size test. -50℃ More preferably, it is 150 J or more.

[0066] In the present invention, in addition to the steel plate having the above toughness value, from the viewpoint of reducing the risk of brittle fracture, it is preferable that the brittle fracture rate is further 0% or more and 5% or less.

[0067] In the present invention, "excellent toughness at low temperatures" refers to a full-size Charpy absorbed energy (vE -50℃) is 100 J or more, and the brittle fracture rate is 5% or less. The above Charpy absorbed energy and brittle fracture rate can be measured by the method described in the examples below.

[0068] <Steel sheet manufacturing method> Next, an embodiment of a method for producing a steel sheet according to the present invention will be described.

[0069] In the following description of the manufacturing method, unless otherwise specified, the temperature refers to the temperature at a 1 / 4 depth position of the plate thickness in the steel material and the steel plate (i.e., the position of (1 / 4)t when the plate thickness is t (mm)) or at the center of the plate thickness. The temperature at the 1 / 4 depth position of the plate thickness or the center of the plate thickness can be calculated by heat transfer calculation from the surface temperature of the steel plate measured with a radiation thermometer, for example.

[0070] The steel sheet of the present invention can be produced by successively carrying out a hot rolling step, a cooling step, a two-phase region quenching step, and a tempering step under the specific conditions described below. In addition, a γ region quenching step may be provided between the hot rolling step and the two-phase region quenching step.

[0071] [Hot rolling process] First, in the hot rolling process, a steel material is heated and hot rolled to obtain a hot-rolled steel sheet. The heating temperature of the steel material can be set appropriately. For example, when a steel material having the above-mentioned composition is used, the steel material is heated to a heating temperature of 900°C or more and 1250°C or less. In the following description, the heating temperature of this hot rolling process may be referred to as the "first heating temperature."

[0072] The method for producing the steel material is not particularly limited. For example, the steel material can be produced by melting molten steel having the above-mentioned composition and then casting it. Examples of the melting include a converter, an electric furnace, and an induction furnace. Examples of the casting include a continuous casting method and an ingot making-blooming rolling method, and from the viewpoint of productivity, the continuous casting method is preferable. For example, a steel slab can be used as the steel material.

[0073] The steel material may be heated after the steel material obtained by the casting is cooled once, or the steel material may be heated directly without being cooled.

[0074] If the heating temperature of the steel material, i.e., the first heating temperature, is less than 900°C, the load on the rolling mill in the subsequent hot rolling increases due to the high deformation resistance of the steel material, making it difficult to perform the hot rolling. Therefore, the first heating temperature is set to 900°C or higher. On the other hand, if the first heating temperature is higher than 1250°C, oxidation of the steel becomes significant, and the loss of the steel material increases due to the removal of the oxide film caused by the oxidation, resulting in a decrease in yield. Therefore, the first heating temperature is set to 1250°C or lower. The first heating temperature is preferably set to 1200°C or lower.

[0075] After the heating, the steel material is hot-rolled to obtain a hot-rolled steel sheet. The final thickness of the hot-rolled steel sheet is not particularly limited, but is preferably 6 mm or more and 50 mm or less, as described above.

[0076] [Cooling process] After the hot rolling step, a cooling step is performed. In the cooling step, the hot-rolled steel sheet is cooled after the hot rolling step and before the two-phase region quenching step described below, or after the hot rolling step and before the γ region quenching step described below. The cooling method is not particularly limited, and examples thereof include air cooling and water cooling.

[0077] [Gamma range quenching process] (optional process) In the present invention, after the completion of the cooling step and before the two-phase region quenching step described below, a γ region quenching step can be performed as necessary. In this step, the cooled hot-rolled steel sheet is reheated to a heating temperature of the γ region, held in the γ region for a given time, and then quenched by accelerated cooling. In the following description, the heating temperature of this γ region quenching step is sometimes referred to as the "second heating temperature."

[0078] Specifically, in the gamma region quenching process, it is preferable to heat and hold the second heating temperature under conditions such that the temperature at the center of the plate thickness is equal to or higher than the Ac3 point and lower than 1000°C, and then quench the hot-rolled steel plate by accelerated cooling under conditions such that the average cooling rate in the temperature range of 700°C to 500°C at a depth position of 1 / 4 of the plate thickness from the surface of the steel plate in the plate thickness direction is 3°C / sec or more, and the cooling end temperature at the temperature at a depth position of 1 / 4 of the plate thickness is lower than 300°C.

[0079] Second heating temperature: Ac3 point or higher and less than 1000℃ The second heating temperature is preferably set to Ac3 point or higher and lower than 1000°C. In order to prevent the formation of an excessively soft ferrite phase and suppress a lack of strength, the second heating temperature (°C) is set to Ac3 point or higher. It is more preferable that the second heating temperature is set to (Ac3 point + 30°C) or higher. In addition, in order to prevent excessive coarsening of grains, which increases the risk of brittle fracture and makes it impossible to obtain the desired toughness, the second heating temperature is set to lower than 1000°C. It is more preferable that the second heating temperature is set to 950°C or lower.

[0080] After the temperature at the center of the thickness of the hot-rolled steel sheet reaches the second heating temperature, the sheet is held at the second heating temperature for 30 minutes. The holding time is not particularly specified, but from the viewpoint of material uniformity (i.e., stabilization of toughness), the holding time is preferably set to 10 to 60 minutes. By setting the holding time to 10 minutes or more, the material can be uniformed. By setting the holding time to 60 minutes or less, an effect of not significantly impairing production efficiency can be obtained.

[0081] Average cooling rate in the temperature range below 700℃ and above 500℃: 3℃ / sec or more The average cooling rate in the above temperature range is preferably 3°C / sec or more. If the average cooling rate in the above temperature range during quenching in the gamma range is less than 3°C / sec, the crystal grains will become coarse, and it may be difficult to obtain sufficient toughness. The average cooling rate in the above temperature range is more preferably 5°C / sec or more.

[0082] On the other hand, the upper limit of the average cooling rate in the above temperature range is not particularly limited. If the average cooling rate in the above temperature range is higher than 200°C / sec, it becomes difficult to control the temperature at each position in the steel sheet, and the material tends to vary in the sheet width direction and rolling direction. As a result, the material properties such as tensile properties and toughness tend to vary. For these reasons, the average cooling rate in the above temperature range is preferably 200°C / sec or less, more preferably 150°C / sec or less, and even more preferably 50°C / sec or less.

[0083] Cooling end temperature: less than 300℃ The cooling end temperature is preferably less than 300°C. In quenching in the gamma region, if the cooling end temperature is 300°C or more at a depth of 1 / 4 of the plate thickness, the amount of solute C in the finally obtained island martensite exceeds 0.4%, and the desired toughness cannot be obtained. Therefore, the cooling end temperature is less than 300°C at a depth of 1 / 4 of the plate thickness. It is more preferable that the cooling end temperature is 200°C or less. There is no particular lower limit to the cooling end temperature, but from the viewpoint of manufacturing efficiency, it is preferable that it is 100°C or more.

[0084] The cooling treatment in the quenching is not particularly limited and can be performed by any method. For example, air cooling and / or water cooling can be used as the cooling treatment. For water cooling, any cooling method using water can be used, such as spray cooling, mist cooling, laminar cooling, etc.

[0085] In the γ-region quenching process, accelerated cooling is performed under the conditions described above, so that the hot-rolled steel sheet can be well quenched.

[0086] [Two-phase hardening process] After the cooling step, a two-phase region quenching step is performed. When the above-mentioned gamma region quenching step is performed after the cooling step, the two-phase region quenching step is performed after the gamma region quenching step. In this two-phase region quenching step, the cooled hot-rolled steel sheet or the gamma region quenched hot-rolled steel sheet is heated to a two-phase region temperature, held at the two-phase region temperature for a given period of time, and then accelerated cooled to perform quenching. In the following description, the heating temperature in this two-phase region quenching step may be referred to as the "third heating temperature."

[0087] Specifically, in the two-phase region quenching process, the temperature is raised from Ac1 point to (Ac1 point + 50°C) at the center of the plate thickness for 2000 seconds or less, and the heating temperature (i.e., the third heating temperature) is maintained at the center of the plate thickness in a two-phase region temperature range of (Ac1 point + 50°C) or more and less than Ac3 point.Then, the hot-rolled steel plate is quenched by accelerated cooling under conditions such that the average cooling rate in the temperature range of 700°C or less and 500°C or more at a depth of 1 / 4 of the plate thickness from the surface of the steel plate in the plate thickness direction is 3°C / second or more, and the cooling end temperature at a depth of 1 / 4 of the plate thickness is less than 500°C.

[0088] Heating time from Ac1 point to (Ac1 point + 50℃): 2000 seconds or less During the temperature rise, the time required to raise the temperature from Ac1 point to (Ac1 point + 50°C) is set to 2000 seconds or less. If the temperature rise time exceeds 2000 seconds, the concentration of C in the reverse transformation austenite region that will eventually become island martensite becomes excessive, and as a result, the amount of solute C in the island martensite may exceed 0.4% even after the tempering process described below. The temperature rise time is preferably 1800 seconds or less. If the temperature rise time is less than 200 seconds, the island martensite formed by the two-phase region quenching is easily decomposed by tempering, so the temperature rise time is preferably 200 seconds or more. The temperature rise time is more preferably 500 seconds or more, and even more preferably 800 seconds or more.

[0089] Third heating temperature: (Ac1 point + 50℃) or more and less than Ac3 point The third heating temperature (℃) is set to the two-phase region temperature range of (Ac1 point + 50℃) or more and less than Ac3 point. If the third heating temperature is less than (Ac1 point + 50℃), reverse transformation does not occur sufficiently, and as a result, island martensite cannot be obtained and a low yield ratio cannot be achieved. Therefore, the third heating temperature is set to (Ac1 point + 50℃) or more.

[0090] On the other hand, if the third heating temperature is Ac3 point or higher, the entire structure undergoes reverse transformation and no ferrite remains. As a result, the ferrite fraction becomes less than 5%, and a low yield ratio cannot be achieved. Therefore, the third heating temperature is set to less than the Ac3 point. It is more preferable that the third heating temperature is set to (Ac3 point - 10°C) or lower.

[0091] Any heating method can be used for the heating in the two-phase region quenching step as long as the third heating temperature can be controlled as described above. One example of the heating method is furnace heating. This furnace heating is not particularly limited, and a general heat treatment furnace can be used.

[0092] After the third heating temperature, which is the two-phase temperature range, is reached, the third heating temperature may be held for an arbitrary time, and then cooling may be started. Although the desired properties can be achieved regardless of the holding time, from the viewpoint of further reducing the yield ratio, the holding time in this two-phase region quenching step is preferably 5 minutes or more, and from the viewpoint of manufacturing efficiency, the holding time is preferably 120 minutes or less.

[0093] Here, the Ac1 point can be determined by the following formula (1). Ac1 point (℃) = 750.8 - 26.6 x C + 17.6 x Si - 11.6 x Mn - 22.9 x Cu - 23 x Ni + 24.1 x Cr + 22.5 x Mo - 39.7 x V - 5.7 x Ti + 232.4 x Nb - 169.4 x Al … (1) Moreover, the Ac3 point can be determined by the following formula (2). Ac3(℃)=937.2-436.5×C+56×Si-19.7×Mn-16.3×Cu-26.6×Ni-4.9×Cr+38.1×Mo+124.8×V+136.3×Ti-19.1×Nb+198.4×Al+3315×B …(2) In the formulas (1) and (2), each element symbol represents the content (mass%) of the corresponding element in the steel, and the content of an element that is not contained in the steel is set to 0.

[0094] Average cooling rate in the temperature range below 700℃ and above 500℃: 3℃ / sec or more The average cooling rate in the temperature range of 700°C or less and 500°C or more at a depth position of 1 / 4 of the plate thickness is 3°C / sec or more. If the average cooling rate is less than 3°C / sec, the crystal grains will become coarse, and it may be difficult to obtain sufficient toughness. The average cooling rate in the above temperature range is preferably 5°C / sec or more, and more preferably 7°C / sec or more.

[0095] The upper limit of the average cooling rate in the above temperature range is not particularly limited. From the viewpoint of production load, the average cooling rate in the above temperature range is preferably 150° C. / sec or less, more preferably 100° C. / sec or less, and even more preferably 50° C. / sec or less.

[0096] Cooling end temperature: less than 500℃ The cooling end temperature is less than 500°C at a depth of 1 / 4 of the plate thickness. If the cooling end temperature is higher than 500°C, the amount of solute C in the island martensite will be 0.4% or more. This will result in a decrease in toughness. The cooling stop temperature is more preferably 300°C or less. On the other hand, there is no particular lower limit for the cooling end temperature, but from the viewpoint of manufacturing efficiency, it is preferably 50°C or more, and more preferably 100°C or more. The cooling treatment in quenching is the same as described above, so a description thereof will be omitted.

[0097] [Tempering process] After the above-mentioned two-phase region quenching process is completed, a tempering process is carried out.

[0098] Specifically, the hot-rolled steel sheet that has been quenched in the two-phase region is tempered under conditions that the temperature at the center of the sheet thickness is 100°C or more and less than 300°C (tempering temperature). If the tempering temperature is less than 100°C, the effect of tempering is not obtained, and the desired toughness is not obtained. The tempering temperature is preferably 120°C or more, and more preferably 130°C or more. On the other hand, if the tempering temperature is 300°C or more, the island martensite decomposition rate is 50% or more. As a result, the desired low yield ratio is not obtained. The tempering temperature is preferably 280°C or less, and more preferably 260°C or less.

[0099] The holding time at the tempering temperature is not particularly specified. From the viewpoint of improving toughness, it is preferable to hold the hot-rolled steel sheet at the tempering temperature for 5 minutes or more. The holding time is preferably 60 minutes or less.

[0100] As described above, when the steel plate of the present invention having the above-mentioned microstructure and properties is used for manufacturing, for example, a liquefied gas storage tank for a ship, it becomes possible to carry out mechanical stress removal instead of post-weld heat treatment as a method for stress relief after welding of the steel plate. Therefore, the steel plate of the present invention can be suitably used as a steel material for a large-scale low-temperature liquefied storage tank. EXAMPLES

[0101] The present invention will be specifically described below based on examples. Note that the present invention is not limited to these embodiments. In these examples, steel sheets were produced according to the procedure described below, and the properties of the obtained steel sheets were evaluated.

[0102] First, molten steel having the composition shown in Table 1 was melted in a converter, and a steel slab (thickness: 200 mm) was produced as a steel material by continuous casting. Note that blank spaces in Table 1 indicate that an element was not intentionally added, and include not only cases where an element is not contained (i.e., the content is 0%), but also cases where an element is unavoidably contained. Additionally, Table 1 also lists the Ac1 point and Ac3 point (°C) calculated using the above-mentioned formulas (1) and (2).

[0103] [Table 1]

[0104] Next, the obtained steel slab was heated and hot rolled according to the manufacturing conditions shown in Table 2 to obtain hot-rolled steel sheets having the thicknesses (final thicknesses) shown in Table 2. The hot-rolled steel sheets were then cooled and heat-treated (quenching and tempering processes) to produce the steel sheets of the present invention. Note that the second heating temperature in the γ region quenching process, the two-phase region quenching process, and the holding time at the tempering temperature were set within the above-mentioned numerical ranges.

[0105] [Table 2]

[0106] For each of the obtained steel sheets, (1) microstructure, (2) tensile strength (TS), (3) yield ratio (YR), and (4) toughness were evaluated according to the following methods. The evaluation results are shown in Table 3.

[0107] (1) Microstructure A test piece for microstructure observation was taken from each steel plate so that the observation position was at a depth of 1 / 4 of the plate thickness. The test piece was embedded in resin so that the cross section perpendicular to the rolling direction was the observation surface, and was mirror-polished. Next, after performing nital etching, the structure was observed with a scanning electron microscope at a magnification of 5000 times and an image of the structure was taken. The obtained image was analyzed to identify the microstructure fraction. Note that an explanation of each structure is omitted here as it has been described above.

[0108] The amount of solute C in the island martensite was measured as follows. The test specimens were used to measure the amount of C by a field emission electron probe micro analyzer (FE-EPMA). The island martensite regions were observed in 10 fields of view, and the average value of the results was taken as the amount of solute C (mass%).

[0109] The decomposition rate of island martensite was measured as follows. Among the island martensite regions identified as described above, those in which precipitation of carbides due to tempering was confirmed were judged to be "decomposed island martensite". This judged region is the above-mentioned "island martensite in a state in which carbides have been precipitated by tempering". The ratio (area ratio) of the decomposed island martensite to the total island martensite was defined as the island martensite decomposition ratio.

[0110] The average thickness of the crystal grains was determined as follows. A structural analysis was performed using EBSD, and the area surrounded by high-angle grain boundaries with a misorientation of 15 degrees or more in a total area of ​​1 mm x 1 mm was defined as a crystal grain. The thickness of the crystal grain (i.e., the length of the crystal grain in the plate thickness direction) was obtained at 50 μm pitches using the intercept method, and the average of these was taken as the average thickness of the crystal grain.

[0111] (2) Tensile strength A JIS No. 4 tensile test piece was taken perpendicular to the rolling direction from a depth position of 1 / 4 of the plate thickness of the steel plate. Using this tensile test piece, a tensile test was carried out in accordance with the provisions of JIS Z2241 (2022) to evaluate the tensile strength (TS) of the steel plate. Here, a tensile strength of 690 MPa or more was evaluated as high strength and "passed."

[0112] (3) Yield ratio As explained above for tensile strength, the yield strength (YS) of the steel plate was calculated from the tensile test results, and the yield ratio (YR) expressed as YS / TS was also evaluated. Here, if the yield ratio was 0.8 or less, it was evaluated as a low yield ratio and was deemed to be "passed."

[0113] (4) Toughness The Charpy absorbed energy and the brittle fracture rate can be regarded as indicators of the toughness of a steel plate. Therefore, in the present invention, the Charpy absorbed energy (vE -50℃ ) and brittle fracture rate were used.

[0114] V-notch test pieces were taken from the 1 / 4 depth position of the steel plate thickness in parallel to the rolling direction in accordance with the provisions of JIS Z2242 (2023). Using these V-notch test pieces, Charpy impact tests were carried out in accordance with the provisions of JIS Z2242 (2023), and the Charpy absorbed energy (vE -50℃ ) and brittle fracture rate were calculated.

[0115] The Charpy impact test was performed by taking three test pieces from each steel plate. The absorbed energy and brittle fracture rate were measured, and the average of the three measured values ​​was recorded as "vE -50℃ In this full-size Charpy impact test, the vE -50℃ If the Charpy fracture strength was 100 J or more and the brittle fracture rate was 5% or less, the specimen was evaluated as having excellent Charpy toughness (i.e., excellent toughness at low temperatures), and was rated as "passed."

[0116] [Table 3]

Claims

1. In mass percent, C: 0.02% or more and 0.15% or less, Si: 0.01% or more and 0.50% or less, Mn: 0.05% or more and 2.50% or less, Ni: 0.50% or more and less than 5.00%; P: 0.03% or less, S: 0.005% or less, and N: 0.0080% or less The balance is Fe and unavoidable impurities, The microstructure at a depth of 1 / 4 of the plate thickness from the surface of the steel plate in the plate thickness direction is In terms of area ratio, the ferrite fraction is 5 to 95%, the island martensite fraction is 1 to 30%, and the remainder is tempered martensite and / or bainite, The steel plate has an amount of solute C in the island martensite of less than 0.4% and a decomposition rate of the island martensite of less than 50%.

2. The composition further includes, in mass%, Al: 0.100% or less, Nb: 0.1% or less, Cr: 2.00% or less, Mo: 1.0% or less, Cu: 2.00% or less, V: 0.10% or less, Ti: 0.03% or less, B: 0.0050% or less, Ca: 0.0070% or less, REM: 0.010% or less, Mg: 0.0070% or less, and Zr: 0.0050% or less The steel sheet according to claim 1 , comprising one or more selected from the following:

3. The steel sheet according to claim 1 , wherein the microstructure has an average crystal grain thickness of 30 μm or less.

4. The steel sheet according to claim 2 , wherein the microstructure has an average crystal grain thickness of 30 μm or less.

5. A method for producing a steel sheet according to any one of claims 1 to 4, A steel material having the above-mentioned composition is heated and hot-rolled to obtain a hot-rolled steel sheet; Next, the hot-rolled steel sheet is subjected to Ac 1 From the point (Ac 1 The heating time to the point +50°C) is 2000 seconds or less, and the heating temperature is the temperature at the center of the plate thickness (Ac 1 point +50℃) or more Ac 3 and then performing a two-phase region quenching process in which the temperature is held at a temperature in a two-phase region below the temperature point, and then accelerated cooling is performed under conditions in which the average cooling rate in the temperature range of 700°C to 500°C at a temperature of 1 / 4 of the plate thickness is 3°C / sec or more, and the cooling end temperature is less than 500°C at a temperature of 1 / 4 of the plate thickness. Next, a tempering step is performed in which the steel plate is tempered at a tempering temperature of 100°C or higher and lower than 300°C at the center of the plate thickness.

6. Prior to the two-phase region quenching step, The hot-rolled steel sheet is heated to a temperature of Ac at the center of the thickness. 3 6. The method for producing a steel sheet according to claim 5, further comprising the steps of: heating and holding the steel sheet at a heating temperature of from 700°C to 500°C at a depth of ¼ of the sheet thickness; and then performing accelerated cooling under conditions in which the average cooling rate in a temperature range of from 700°C to 500°C is 3°C / sec or more at a temperature of from 1 / 4 of the sheet thickness to a cooling end temperature of less than 300°C at a temperature of from 1 / 4 of the sheet thickness to a depth of ¼ of the sheet thickness.

Citation Information

Patent Citations

  • Low yield ratio high strength steel having excellent toughness and weldability

    JP2004315925A

  • Steel material for line pipe

    JP2012017522A

  • Super low yield ratio high tensile strength thick steel sheet and manufacturing method therefor

    JP2019119934A

  • Steel plate and its manufacturing method

    JP7338811B1

  • High-strength steel sheet with excellent cryogenic toughness and low yield ratio and method for producing the same

    JP2016507649A